A sodium ion battery positive electrode material and its preparation method and application
By using a new double-layer stirring paddle and a titanium-doped zirconium-coated method in the preparation process of sodium ion battery positive electrode materials, the problem of poor structural stability of manganese-rich positive electrode materials and prone to cracks in large-particle precursors is solved, and a higher level of cycling stability and specific capacity, and reduce production energy consumption.
Patent Information
- Application Number
- CN202310170767.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-27
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-02-27
AI Technical Summary
The structural stability of manganese-rich positive electrode materials is poor, and precursor particles with large particles with high specific surface area are prone to cracks during the production process, and the co-precipitation and stirring equipment consumes a high energy.
A new double-layer stirring paddle was used to perform the co-precipitation reaction, and a sodium ion battery positive electrode material with high circulation stability was prepared by doping titanium-coated zirconium.
It significantly improves the crack phenomenon in the production process of large-particle precursors, reduces energy consumption by 40%, and improves the cycle stability and specific capacity of the cathode material.
Smart Images

Figure CN116143196B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries and relates to a sodium ion battery positive electrode material and a preparation method and application thereof. Background Art
[0002] Today, chemical energy storage is still dominated by lithium-ion batteries. However, lithium batteries are widely used in 3C digital products, power vehicles, etc., and the lithium content in the earth's crust is not high, which makes the current price of lithium carbonate high, which has greatly restricted the development of the energy storage industry.
[0003] Sodium-ion batteries and lithium-ion batteries have similar properties. Although the specific capacity of sodium-ion batteries is lower than that of lithium-ion batteries, sodium ions are almost inexhaustible, which makes the cost of sodium-ion batteries hugely advantageous over that of lithium-ion batteries. Therefore, sodium-ion batteries have great application prospects in the energy storage industry and low-speed electric vehicles.
[0004] Among them, the positive electrode material is an important factor that determines a series of key indicators of sodium-ion batteries, such as energy density, cycle performance, and cost. The precursor is the main raw material for preparing the positive electrode material of the battery. The physical and chemical indicators of the precursor, such as morphology, particle size, specific surface area, and tap density, largely determine the performance of the precursor material.
[0005] CN108565457A discloses a sodium ion battery positive electrode material, a preparation method thereof and a sodium ion battery. The sodium ion battery positive electrode material is spherical in shape, wherein the concentrations of manganese and nickel are distributed in a gradient manner along the radial direction.
[0006] CN115692653A discloses a sodium ion battery positive electrode material and a preparation method thereof. The positive electrode material comprises a core body and a coating layer coating the core body, wherein a doping layer is provided between the core body and the coating layer. The core body is a layered metal oxide, and the coating layer is a metal oxide. Metal ions in the coating layer penetrate into the core body for doping to form a doping layer.
[0007] The manganese-rich positive electrode material has poor structural stability, which leads to poor battery cycle stability; large-particle, high-specific-surface-area precursor particles are prone to cracking during the production process, which affects product performance; current co-precipitation stirring equipment consumes a lot of energy. Summary of the invention
[0008] The object of the present invention is to provide a sodium ion battery positive electrode material and a preparation method and application thereof. The present invention aims to solve the problem that the structure stability of manganese-rich positive electrode materials is poor and large-particle and high-specific-surface-area precursor particles are prone to cracking during the production process. A new double-layer stirring paddle is used for stirring, and a sodium ion battery positive electrode material with high cycle stability is prepared by a method of doping titanium and coating zirconium.
[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a method for preparing a positive electrode material for a sodium ion battery, the preparation method comprising the following steps:
[0011] (1) adding a nickel-manganese mixed solution, a precipitant, a complexing agent and a titanium source solution to a base solution in parallel, and performing a coprecipitation reaction under stirring with a double-layer stirring paddle to obtain a precursor;
[0012] (2) The precursor is mixed with a sodium source, calcined, and then mixed with a zirconium source solution, and sintered to obtain the sodium ion battery positive electrode material.
[0013] The present invention improves the cracking problem in the production process of large-particle precursors and reduces energy consumption by 40% by combining two new blades (upper wing-shaped blades and lower rigid-flexible blades). By doping a small amount of Ti and coating ZrO2 to improve the stability of the structure and the specific capacity, the positive electrode material obtains better cycle stability and higher specific capacity.
[0014] Preferably, the molar ratio of nickel to manganese in the nickel-manganese mixed solution in step (1) is x:y, x+y=1, 0.2 <x<0.4。
[0015] Preferably, the total ion concentration of the nickel-manganese mixed solution is 1.6-2.4 mol / L, for example, 1.6 mol / L, 1.8 mol / L, 2 mol / L, 2.2 mol / L or 2.4 mol / L.
[0016] Preferably, the precipitant comprises liquid alkali.
[0017] Preferably, the concentration of the precipitant is 9-12 mol / L, for example, 9 mol / L, 10 mol / L, 11 mol / L or 12 mol / L.
[0018] Preferably, the complexing agent comprises aqueous ammonia.
[0019] Preferably, the concentration of the complexing agent is 8 to 10 mol / L;
[0020] Preferably, the titanium source comprises titanyl sulfate;
[0021] Preferably, the concentration of the titanium source solution is 0.2-0.25 mol / L.
[0022] Preferably, the molar ratio of the feed metals of the nickel-manganese mixed solution and the titanium source solution is (200-1000):1, for example: 200:1, 400:1, 500:1, 800:1 or 1000:1, etc.
[0023] Preferably, the base solution in step (1) comprises a precipitant solution and / or a complexing agent solution.
[0024] Preferably, the concentration of aqueous ammonia in the base solution is 12-14 g / L, for example, 12 g / L, 12.5 g / L, 13 g / L, 13.5 g / L or 14 g / L.
[0025] Preferably, nitrogen protective gas is introduced into the base liquid.
[0026] Preferably, the double-layer stirring paddle in step (1) comprises an upper-layer airfoil blade and a lower-layer rigid-flexible combined blade.
[0027] Preferably, the upper airfoil blades are designed in combination with aircraft wings and ship propulsion blades, and the lower rigid-flexible combined blades are six-blade open turbine rigid-flexible stirring blades.
[0028] The variable annular volume optimized airfoil stirring paddle in the double-layer stirring paddle of the present invention can improve the macroscopic mixing effect, maintain the axial flow velocity, and increase the fluid strain rate. The rigid-flexible stirring paddle can improve the microscopic mixing effect, maintain the radial flow velocity, reduce the shear force, and improve the cracks of the large particle precursor.
[0029] Preferably, the stirring speed of the double-layer stirring paddle is 160-320 rpm, for example, 160 rpm, 180 rpm, 200 rpm, 250 rpm or 320 rpm.
[0030] Preferably, the coprecipitation reaction temperature is 40-60°C, for example, 40°C, 45°C, 50°C, 55°C or 60°C.
[0031] Preferably, the pH of the coprecipitation reaction is 9-12, for example, 9, 10, 11 or 12.
[0032] Preferably, the median particle size D50 of the precursor is 7 to 25 μm, for example, 7 μm, 10 μm, 12 μm, 15 μm, 20 μm or 25 μm.
[0033] Preferably, the coprecipitation reaction in step (1) is followed by centrifugation, washing, drying and demagnetization.
[0034] Preferably, the sodium source in step (2) comprises sodium carbonate.
[0035] Preferably, the calcination temperature is 800-900°C, for example, 800°C, 820°C, 850°C, 880°C or 900°C.
[0036] Correspondingly, the calcination treatment time is 10 to 15 hours, for example: 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours.
[0037] Preferably, the zirconium source solution in step (2) comprises a n-propanol solution of zirconium n-propoxide.
[0038] Preferably, the mass fraction of the zirconium salt in the zirconium source solution is 60-80%, for example, 60%, 65%, 70%, 75% or 80%.
[0039] Preferably, the sintering temperature is 400-600°C, for example, 400°C, 450°C, 500°C, 550°C or 600°C.
[0040] Preferably, the sintering treatment time is 4 to 6 hours, for example: 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours.
[0041] In a second aspect, the present invention provides a sodium ion battery positive electrode material, which is prepared by the method described in the first aspect, and the sodium ion battery positive electrode material comprises a titanium-doped sodium nickel manganese oxide core and a zirconium oxide coating layer arranged on the surface of the titanium-doped sodium nickel manganese oxide core.
[0042] In a third aspect, the present invention provides a positive electrode plate, wherein the positive electrode plate comprises the sodium ion battery positive electrode material as described in the second aspect.
[0043] In a fourth aspect, the present invention provides a sodium ion battery, wherein the sodium ion battery comprises the positive electrode sheet as described in the third aspect.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] (1) The present invention utilizes the lower radial rigid-flexible combined blades to increase the micro-mixing effect, reduce the blade shear force and improve particle cracks, and increases the macroscopic axial flow velocity through the upper airfoil blades, so that the fluid in the kettle is mixed evenly and the stirring energy consumption is greatly reduced.
[0046] (2) The present invention improves the structural stability of the precursor sintered positive electrode material and increases the specific capacity by doping Ti and coating Zr.
[0047] (3) The present invention reduces the consumption of the co-precipitation process by 40% by adopting a newly designed double-layer blade, and significantly improves the cracking phenomenon in the production process of large-particle precursors; and through titanium-doped zirconium coating, the 100-cycle retention rate is increased from 74% to 91.4%. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is a SEM image of the sodium ion battery positive electrode precursor described in Example 1.
[0049] Figure 2 This is a SEM image of the sodium ion battery positive electrode precursor described in Comparative Example 1.
[0050] Figure 3 It is a schematic diagram of the structure of the double-layer stirring paddle described in Example 1, wherein 1-2 is a main view, 3 is a top view, and 4 is an oblique view. DETAILED DESCRIPTION
[0051] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0052] Example 1
[0053] This embodiment provides a sodium ion battery positive electrode material, and the preparation method of the sodium ion battery positive electrode material is as follows:
[0054] (1) A sulfate solution A containing nickel ions and manganese ions and having a total ion concentration of 2 mol / L is prepared, wherein the molar ratio of nickel ions to manganese ions is 30:70, an industrial liquid alkali with a concentration of 10 mol / L is used as a precipitant solution B, an ammonia solution with a concentration of 10 mol / L is used as a complexing agent solution C, and a titanyl sulfate solution D with a concentration of 0.2 mol / L is used, a base solution E containing the precipitant solution and the complexing agent solution is prepared in a reactor, the ammonia concentration of E is 13 g / L, and nitrogen is introduced as a protective gas, the mixed salt solution A, the precipitant solution B and the complexing agent solution C are added to the reactor in parallel, the feed metal molar ratio of the nickel-manganese mixed solution to the titanium source solution is 800:1, a coprecipitation reaction is carried out at a speed of 200 rpm using a newly designed double-layer stirring paddle, the reaction pH is controlled at 11, and the temperature is controlled at 50° C., to obtain a precursor with a particle size of 12 μm as the target particle size D50, and the SEM image of the precursor is as shown in FIG. Figure 1 As shown;
[0055] (2) After the precursor is centrifuged, washed, dried, and magnetic foreign matter is removed, the precursor powder is uniformly mixed with Na2CO3 powder at Na / M=1.1:1, calcined in an air atmosphere at 850°C for 12 hours, 70% of zirconium n-propoxide is dissolved in n-propanol for dilution, and then the positive electrode material is added to the solution, stirred sufficiently, and then placed in an oven to dry at 100°C. The dried powder is then kept at 500°C in an air atmosphere for 5 hours, and the sodium ion battery positive electrode material is obtained after grinding and sieving.
[0056] Example 2
[0057] This embodiment provides a sodium ion battery positive electrode material, and the preparation method of the sodium ion battery positive electrode material is as follows:
[0058] (1) preparing a sulfate solution A containing nickel ions and manganese ions and having a total ion concentration of 2.2 mol / L, wherein the molar ratio of nickel ions to manganese ions is 35:65, using an industrial liquid alkali with a concentration of 10 mol / L as a precipitant solution B, using 9 mol / L ammonia water as a complexing agent solution C, and using a titanyl sulfate solution D with a concentration of 0.2 mol / L, preparing a base solution E containing the precipitant solution and the complexing agent solution in a reactor, wherein the ammonia water concentration of E is 13.5 g / L, and introducing nitrogen as a protective gas, and adding the mixed salt solution A, the precipitant solution B and the complexing agent solution C to the reactor in parallel, wherein the feed metal molar ratio of the nickel-manganese mixed solution to the titanium source solution is 600:1, and carrying out a coprecipitation reaction with a newly designed double-layer stirring paddle at a speed of 200 rpm, the reaction pH is controlled at 10.5, and the temperature is controlled at 55° C., to obtain a precursor with a particle size of 15 μm as a target particle size D50;
[0059] (2) After the precursor is centrifuged, washed, dried, and magnetic foreign matter is removed, the precursor powder is uniformly mixed with Na2CO3 powder at Na / M=1.1:1, calcined in an air atmosphere at 880°C for 12 hours, 72% of zirconium n-propoxide is dissolved in n-propanol for dilution, and then the positive electrode material is added to the solution, stirred sufficiently, and then placed in an oven to dry at 100°C. The dried powder is then kept at 550°C in an air atmosphere for 5 hours, and the sodium ion battery positive electrode material is obtained after grinding and sieving.
[0060] Example 3
[0061] The only difference between this embodiment and embodiment 1 is that the molar ratio of the feed metals of the nickel-manganese mixed solution and the titanium source solution is controlled to be 100:1, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0062] Example 4
[0063] The only difference between this embodiment and embodiment 1 is that the molar ratio of the feed metals of the nickel-manganese mixed solution and the titanium source solution is controlled to be 1200:1, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0064] Comparative Example 1
[0065] This comparative example provides a sodium ion battery positive electrode material, and the preparation method of the sodium ion battery positive electrode material is as follows:
[0066] (1) A sulfate solution A containing nickel ions and manganese ions and having a total ion concentration of 2 mol / L is prepared, wherein the molar ratio of nickel ions to manganese ions is 30:70, an industrial liquid alkali with a concentration of 10 mol / L is used as a precipitant solution B, and an ammonia solution with a concentration of 1 mol / L is used as a complexing agent solution C. A base solution E containing the precipitant solution and the complexing agent solution is prepared in a reactor, wherein the ammonia solution concentration of E is 13 g / L, and nitrogen is introduced as a protective gas. The mixed salt solution A, the precipitant solution B and the complexing agent solution C are added to the reactor in parallel, and a coprecipitation reaction is carried out at a speed of 300 rpm using a common stirring paddle. The pH of the reaction is controlled at 10 and the temperature is 50° C. to obtain precursor particles with a particle size of 12 μm and a target particle size D50. The SEM image of the precursor particles is as shown in FIG. Figure 2 As shown;
[0067] (2) After the precursor is subjected to treatments such as centrifugation, washing, drying, and removal of magnetic foreign matter, the precursor powder is uniformly mixed with Na2CO3 powder at a ratio of Na / M=1.1:1, and calcined in an air atmosphere at 850°C for 12 hours to obtain the sodium ion battery positive electrode material.
[0068] Comparative Example 2
[0069] The only difference between this comparative example and Example 1 is that a conventional stirring paddle is used, and other conditions and parameters are exactly the same as those in Example 1.
[0070] Comparative Example 3
[0071] The only difference between this comparative example and Example 1 is that no titanium source is added, and other conditions and parameters are exactly the same as those in Example 1.
[0072] Comparative Example 4
[0073] The only difference between this comparative example and Example 1 is that zirconium is not coated, and other conditions and parameters are exactly the same as those in Example 1.
[0074] Performance Test:
[0075] Take the positive electrode materials prepared in Examples 1-4 and Comparative Examples 1-4, drop the electrode materials, acetylene black, and polyvinylidene fluoride into N-methyl-2-pyridine alkanone at a mass ratio of 8:1:1 to prepare a solution, then evenly apply it on aluminum foil, dry it, and punch it into a thin sheet. The battery pole piece, elemental sodium sheet, glass fiber separator, electrolyte (NaClO4) gasket, shrapnel and battery shell are assembled into a button battery in an Ar gas glove box, and the battery is tested. The test results are shown in Table 1:
[0076] Table 1
[0077]
[0078] As can be seen from Table 1, from Examples 1-2, the sodium ion battery positive electrode material of the present invention can produce a battery with a 0.1C discharge capacity of more than 142 mAh / g and a 1C discharge capacity of more than 111 mAh / g. After 100 cycles, the capacity retention rate can reach more than 91.4%. The present invention can significantly improve the cycle capacity retention rate by doping Ti and coating Zr in the manganese-rich sodium positive electrode material.
[0079] By comparing Example 1 with Examples 3-4, it can be seen that in the preparation process of the positive electrode material for a sodium ion battery of the present invention, the molar ratio of the feed metal of the nickel-manganese mixed solution and the titanium source solution will affect the titanium doping amount and thus affect the performance of the positive electrode material for a sodium ion battery. The molar ratio of the feed metal of the nickel-manganese mixed solution and the titanium source solution is controlled at 200 to 1000:1, and the performance of the positive electrode material for a sodium ion battery is better. If the molar amount of the feed metal of the titanium source solution is too large, the discharge specific capacity of the positive electrode material is significantly reduced. If the molar amount of the feed metal of the titanium source solution is too small, the cycle retention rate improvement effect is poor.
[0080] By comparing Example 1 with Comparative Example 1, it can be seen that the present invention improves the crack problem in the production process of large-particle precursors and reduces energy consumption by 40% by combining two new blades (upper wing-shaped blades and lower rigid-flexible blades). By doping a small amount of Ti and coating ZrO2 to improve the stability of the structure and the specific capacity, the positive electrode material obtains better cycle stability and higher specific capacity.
[0081] By comparing Example 1 and Comparative Example 2, it can be seen that the variable annular optimized airfoil stirring paddle in the double-layer stirring paddle of the present invention can improve the macroscopic mixing effect, maintain the axial flow velocity, and increase the fluid strain rate. The rigid-flexible stirring paddle can improve the microscopic mixing effect, maintain the radial flow velocity, reduce the shear force, and improve the cracks of large particle precursors.
[0082] From the comparison between Example 1 and Comparative Examples 3-4, it can be seen that the present invention improves the structural stability of the precursor sintered positive electrode material and increases the specific capacity by doping Ti and coating Zr.
[0083] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a positive electrode material for a sodium ion battery, characterized in that: The preparation method comprises the following steps: (1) adding a nickel-manganese mixed solution, a precipitant, a complexing agent and a titanium source solution to a base solution in parallel, and performing a coprecipitation reaction under stirring with a double-layer stirring paddle to obtain a precursor; (2) mixing the precursor with a sodium source, calcining the mixture, and then mixing the mixture with a zirconium source solution, and sintering the mixture to obtain the sodium ion battery positive electrode material; The double-layer impeller in step (1) comprises an upper-layer airfoil blade and a lower-layer rigid-flexible combined blade; the upper-layer airfoil blade is designed in combination with an aircraft wing and a ship propulsion blade, and the lower-layer rigid-flexible combined blade is a six-blade open turbine rigid-flexible impeller.
2. The preparation method according to claim 1, characterized in that The molar ratio of nickel to manganese in the nickel-manganese mixed solution of step (1) is x:y, x+y=1, 0.2 <x<0.4。 3. The preparation method according to claim 1, characterized in that: The total ion concentration of the nickel-manganese mixed solution is 1.2-2.2 mol / L.
4. The preparation method according to claim 1, characterized in that: The precipitant includes liquid alkali.
5. The preparation method according to claim 1, characterized in that: The concentration of the precipitant is 9-12 mol / L.
6. The preparation method according to claim 1, characterized in that: The complexing agent includes aqueous ammonia.
7. The preparation method according to claim 1, characterized in that: The concentration of the complexing agent is 8-10 mol / L.
8. The preparation method according to claim 1, characterized in that: The titanium source includes titanyl sulfate.
9. The preparation method according to claim 1, characterized in that: The concentration of the titanium source solution is 0.2-0.25 mol / L.
10. The preparation method according to claim 1, characterized in that: The molar ratio of the feed metals of the nickel-manganese mixed solution and the titanium source solution is (200-1000):
1.
11. The preparation method according to claim 1, characterized in that: The base solution in step (1) includes a precipitant solution and / or a complexing agent solution.
12. The preparation method according to claim 1, characterized in that: The concentration of ammonia water in the base liquid is 12-14 g / L.
13. The preparation method according to claim 1, characterized in that: A nitrogen protective gas is introduced into the base liquid.
14. The preparation method according to claim 1, characterized in that: The stirring speed of the double-layer stirring paddle is 160-320 rpm.
15. The preparation method according to claim 1, characterized in that: The temperature of the coprecipitation reaction is 40-60°C.
16. The preparation method according to claim 1, characterized in that: The pH of the coprecipitation reaction is 9-12.
17. The preparation method according to claim 1, characterized in that: The median particle size D50 of the precursor is 7 to 25 μm.
18. The preparation method according to claim 1, characterized in that: The coprecipitation reaction in step (1) is followed by centrifugation, washing, drying and demagnetization.
19. The preparation method according to claim 1, characterized in that: The sodium source in step (2) includes sodium carbonate.
20. The preparation method according to claim 1, characterized in that: The calcination temperature is 800-900°C.
21. The preparation method according to claim 1, characterized in that: The calcination treatment time is 10 to 15 hours.
22. The preparation method according to claim 1, characterized in that: The zirconium source solution in step (2) comprises a n-propanol solution of zirconium n-propoxide.
23. The preparation method according to claim 1, characterized in that: The mass fraction of the zirconium salt in the zirconium source solution is 60-80%.
24. The preparation method according to claim 1, characterized in that: The sintering temperature is 400-600°C.
25. The preparation method according to claim 1, characterized in that: The sintering time is 4 to 6 hours.
26. A sodium ion battery positive electrode material, characterized in that: The sodium ion battery positive electrode material is prepared by the method according to any one of claims 1 to 25, and the sodium ion battery positive electrode material comprises a titanium-doped sodium nickel manganese oxide core and a zirconium oxide coating layer arranged on the surface of the titanium-doped sodium nickel manganese oxide core.
27. A positive electrode plate, characterized in that: The positive electrode sheet comprises the sodium ion battery positive electrode material as claimed in claim 26.
28. A sodium ion battery, characterized in that: The sodium ion battery comprises the positive electrode sheet as claimed in claim 27.
Citation Information
Patent Citations
Sodium-ion battery positive electrode material, preparation method thereof and sodium-ion battery
CN108565457A
Positive electrodematerial for sodium ion battery, preparation method thereof and sodium ion battery
CN108987708A
Preparation method of ternary nickel cobalt manganese anode material precursor capable of changing stacking mode of microcrystalline particle
CN109467136A
Spherical-like sodium ion battery positive electrode material, preparation method thereof and sodium ion battery
CN115000399A